An optical coherence tomography-based grading of diabetic maculopathy proposed by an international expert panel: The European School for Advanced Studies in Ophthalmology classification. Issue 1 (January 2020) - Panozzo, Giacomo; Cicinelli, Maria Vittoria; Augustin, Albert J; Battaglia Parodi, Maurizio; Cunha-Vaz, Josè; Guarnaccia, Giuseppe; Kodjikian, Laurent; Jampol, Lee Merrill; Jünemann, Anselm; Lanzetta, Paolo; Löwenstein, Anat; Midena, Edoardo; et al.
Aims: To present an authoritative, universal, easy-to-use morphologic classification of diabetic maculopathy based on spectral domain optical coherence tomography. Methods: The first draft of the project was developed based on previously published classifications and a literature search regarding the spectral domain optical coherence tomography quantitative and qualitative features of diabetic maculopathy. This draft was sent to an international panel of retina experts for a first revision. The panel met at the European School for Advanced Studies in Ophthalmology headquarters in Lugano, Switzerland, and elaborated the final document. Results: Seven tomographic qualitative and quantitative features are taken into account and scored according to a grading protocol termed TCED-HFV, which includes foveal thickness (T), corresponding to either central subfoveal thickness or macular volume, intraretinal cysts (C), the ellipsoid zone (EZ) and/or external limiting membrane (ELM) status (E), presence of disorganization of the inner retinal layers (D), number of hyperreflective foci (H), subfoveal fluid (F), and vitreoretinal relationship (V). Four different stages of the disease, that is, early diabetic maculopathy, advanced diabetic maculopathy, severe diabetic maculopathy, and atrophic maculopathy, are based on the first four variables, namely the T, C, E, and D. The different stages reflect progressive severity of the disease. Conclusion: A novel grading system of diabetic maculopathy is hereby proposed. The classification is aimed at providing a simple, direct, objective tool to classify diabetic maculopathy (irrespective to the treatment status) even for non-retinal experts and can be used for therapeutic and prognostic purposes, as well as for correct evaluation and reproducibility of clinical investigations.